Species affinity and infracommunity ordination of helminths of Leptodactylus chaquensis (Anura: Leptodactylidae) in two contrasting environments from Northeastern Argentina - Kehr, Arturo Ignacio (2006)
One hundred seventy-two frogs (Leptodactylus chaquensis) were collected from November 2002 to November 2003, in agricultural (n = 132) and nonagricultural (n = 40) areas. Both sites are near the city of Corrientes, Argentina. The main goals of this study were as follows: (1) to determine the helminth parasite community in agricultural and nonagricultural habitats; (2) to analyze the relationships between helminth parasites and site of infection, frog body size, and gender; (3) to identify and examine covariation and association of helminth communities; and (4) to determine the mean richness and diversity of parasite communities. The helminth compound community of this amphibian species consisted of 24 species: 19 in agricultural habitats and 18 in nonagricultural habitats. The mean richness, mean diversity, and evenness of helminths were significantly different between the habitats (P < 0.05). The body size of the host was the important factor in determining parasite richness. Both habitats exhibited differences in community ordination. The helminth species in the 2 habitats exhibited the same interspecific relationships, although differences were observed in the intensity of infection.